Pedagogy for the Future in the Context of Nepal: An Exploration with Critical Mathematics Education - Chapai, Krishna Prasad Sharma (Academic Journal of Mathematics Education, 2023)
Critical mathematics education undermines the neutrality of mathematics teaching and learning;it confronts societal barriers and suppression, social justice, and opens up new pathwaysfor students to participate in social and political life. This paper intends to analyze criticalmathematics education and how it can be used as a tool to create a bright future for mathematicsin Nepal by altering teaching pedagogy and applying it to practice. For this study, the searchengine Google, Google scholar, Eric, and ProQuest were used. Three major themes wereexplored: thoughts of teachers towards critical mathematics education, mathematics educationin relation to society, and technology-based teaching. To discuss the result content analysis onthe themes were used. This study finds that optimistic attitude, innovation of teachers, and theuse of critical pedagogy appear to be too responsible for the bright future of mathematics. Toattain the objectives, our teachers must be enthusiastic, knowledgeable about information andtechnology, and critical and reflective.